Architecture as Urban Catalyst: Infographic Design Guideline on Kuala Lumpur Riverfront Revitalisation - Mohd Yusman, Mohamad Qawiem; Shaari, Mariam Felani; Samadi, Zalina; Ali Ariff, Azlan Ariff; Sanchez, Ricardo B (International Journal of Sustainable Construction Engineering and Technology, 2023)
In various areas, communities and localities worldwide, a traversing river plays a vital role as the lifeblood of many dwellings and urban areas. Kuala Lumpur’s expanding urban spaces indicate a thriving economy. Despite this, the rapid development has led to the construction of many residential and commercial buildings along the river, resulting in pollution from domestic, physical, and chemical waste. This pollution poses a threat to urban waste management, impacting both health and the river’s ecosystem. To address this issue, this study endeavours to recommend an updated set of design guidelines for the Dayabumi, Kuala Lumpur riverfront architecture. The recommended guideline will focus on alterations to the river form and build form interventions to achieve the desired results. Through case studies, literature reviews, and observations from developed countries, the study identified best practices for waste management and architectural design. The findings encompass waste management programs and design guidelines covering build form, river form, green coverings, economy injection, and the overall urban environment. By enforcing appropriate regulations and preparing for future waste production, we can protect and revitalize the riverfront at Dayabumi, Kuala Lumpur.